Policy Implementation and Social Functioning of Persons with Disabilities: The Role of Social Support - Achmad, Willya (PLD UIN Sunan Kalijaga, 2025)
Rapid demographic and lifestyle changes have increased the urgency of public policies that respond to the needs of persons with disabilities. This study examines the influence of policy implementation on the social functioning of persons with disabilities, with particular attention to the role of social support. The research was conducted at the Griya Harapan Disabled Social Services Center (PPSGHD) in West Java Province using a quantitative approach and a 5-point Likert scale questionnaire administered to 100 respondents. Data were analyzed using PLS-SEM to assess both the measurement and structural models. The findings indicate that policy implementation significantly improves the social functioning of persons with disabilities but does not directly affect social support. Meanwhile, social support has a significant positive effect on social functioning, underscoring its important role in shaping functional outcomes. These results highlight that effective policy implementation needs to be complemented by strengthened social support to enhance the social functioning of persons with disabilities. Perubahan demografis dan gaya hidup yang cepat meningkatkan urgensi kebijakan publik yang responsif terhadap kebutuhan penyandang disabilitas. Penelitian ini bertujuan mengkaji pengaruh implementasi kebijakan terhadap keberfungsian sosial penyandang disabilitas, dengan perhatian khusus pada peran dukungan sosial. Penelitian dilakukan di Pusat Pelayanan Sosial Griya Harapan Disabilitas (PPSGHD) Provinsi Jawa Barat menggunakan pendekatan kuantitatif melalui kuesioner skala Likert 5 poin yang melibatkan 100 responden. Data dianalisis menggunakan PLS-SEM untuk menguji model pengukuran dan model struktural. Hasil penelitian menunjukkan bahwa implementasi kebijakan berpengaruh signifikan terhadap keberfungsian sosial penyandang disabilitas, namun tidak berpengaruh langsung terhadap dukungan sosial. Sementara itu, dukungan sosial berpengaruh positif dan signifikan terhadap keberfungsian sosial. Temuan ini menegaskan bahwa efektivitas implementasi kebijakan perlu dilengkapi dengan penguatan dukungan sosial untuk meningkatkan keberfungsian sosial penyandang disabilitas.